(Post) Poetic narrative: the metaphorical levels of Grande sertão: veredas. - Tinoco, Robson Coelho (ITINERÁRIOS – Revue de Littérature, 2010)
The production of a literary composition of value, created in the intersection of personal and collective needs, consists of original information, crafted, above all, metaphorically. Such information represents a process of revelation of ideas that tends to be more creative the bolder and more innovative the text is. This boldness and innovation are factors that, dependent on the ethical-aesthetic intention of such an author as Guimarães Rosa, mark the narrative proposal in Grande sertão: veredas. This novel, even if complexly produced under the optics of one given fi gurative construction, appears to be ample and attractive in its levels of literary language, presenting the fi ctional content throughout pages of pure metaphoric narrative poetry.